Fact factories: Wikipedia and the power to represent - Ford, H; Graham, M; Meyer, E (2015)
Wikipedia is no longer just another source of knowledge about the world. It is fast becoming a central source, used by other powerful knowledge brokers like Google and Bing to offer authoritative answers to search queries about people, places and things and as information infrastructure for a growing number of Web applications and services. Researchers have found that Wikipedia offers a skewed representation of the world that favours some groups at the expense of others so that representations on the platform have repercussions for the subjects of those representations beyond Wikipedia's domain. It becomes critical in this context to understand how exactly Wikipedia's representations come about, what practices give rise to them and what socio-technical arrangements lead to their expression. This ethnographic study of Wikipedia explores the values, principles and practices that guide what knowledge Wikipedia represents. It follows the foundational principles of Wikipedia in its identity both as an encyclopaedia and a product of the free and open source software and internet freedom rhetoric of the early 2000s. Two case studies are analysed against the backdrop of this ideology, illustrating how different sets of actors battle to extend or reject the boundaries of Wikipedia, and in doing so, affect who are defined as the experts, subjects and revolutionaries of the knowledge that is taken up. The findings of this thesis indicate that Wikipedia's process of decision-making is neither hierarchical nor is it egalitarian; rather, the power to represent on Wikipedia is rhizoid: it happens at the edges rather than in the centre of the network. Instead of everyone having the same power to represent their views on Wikipedia, those who understand how to perform and speak according to Wikipedia's complex technical, symbolic and policy vocabulary tend to prevail over those who possess disciplinary knowledge about the subject being represented. Wikipedians are no amateurs as many would have us believe; nor are they passive collectors of knowledge held in sources; Wikipedians are, instead, active co-creators of knowledge in the form of facts that they support using specially chosen sources. The authority of Wikipedia and Wikipedians is garnered through the performative acts of citation, through the ability of individual editors to construct the traces that represent citation, and through the stabilization and destabilization of facts according to the ideological viewpoints of its editors. In venerating and selecting certain sources among others, Wikipedians also serve to reaffirm traditional centres of authority, while at the same time amplifying new centres of knowledge and denying the authority of knowledge that is not codified in practice. As a result, Wikipedia is becoming the site of new centres of expertise and authoritative knowledge creation, and is signalling a move towards the professionalization of the expertise required to produce factual data in the context of digital networks.